Vaudou and the marine: Jacques-Stéphen Alexis and Zora Neale Hurston on the American occupation of Haiti. Issue 2 (2nd April 2016) - Heady, Margaret
ABSTRACT: 2015 marked the 100-year anniversary of the beginning of the longest occupation by American forces of an independent nation. In Haiti, the American presence was a catalyst for the development of theories and policies which polarized Haitian society and led to the exile of some of Haiti's most important intellectuals, a legacy which continues into the twenty-first century and which contributed to an increased, if not voluntary, transnational black consciousness. In the USA, a significant if less obvious legacy of the occupation is the role it played in the long process of redefining racial and national identities within our own borders. The destinies of the two nations became intertwined during the occupation years in an unprecedented way, with the marine serving as a contradictory symbol of both democracy and domination. Among the many writers and intellectuals who were inevitably influenced by these events, two in particular, Jacques-Stephen Alexis and Zora Neale Hurston, proved to be prescient and fearless in their drive to cultivate an authentic literary voice for the unrepresented and to use this voice – which for both was epitomized in Haiti through vaudou – as a means of resistance as well as a catalyst for a broader Africana consciousness. What these authors from opposing republics shared, in opposition to intellectual trends of the time, was a sense of the seemingly contradictory need for a nationalism based on the least "significant" members of society and a burgeoning understanding of how that narrow focus paradoxically opened up new vistas of a transnational community. Their portrayals of the aftermath of the American occupation in Tell My Horse and Les Arbres musiciens demonstrate the early development and juggling of this "dual identity" which has come to characterize so many writers of the black Atlantic and beyond.